(untitled) (American Journal of Business Management, Economics and Banking, 2025)
The article analyzes the role and importance of cooperation with international financial institutions in the development of banks’ investment activities. Credit lines, grants, and technical assistance from the World Bank, the Asian Development Bank, the European Bank for Reconstruction and Development, the International Finance Corporation, the Islamic Development Bank, and other financial institutions are considered an important source for increasing the stability of the banking system. The possibilities of attracting long-term resources to the banking sector through international cooperation, developing capital markets, introducing digital technologies, supporting small and medium-sized businesses, and expanding green finance mechanisms will also be substantiated. According to the research results, effective cooperation with international financial institutions strengthens the investment potential of banks and serves the sustainable development of the country’s economy.